Statins for Primary Prevention of Cardiovascular and Cerebrovascular Events in Diabetic Patients without Established Cardiovascular Diseases: A Meta-Analysis - Chen, Y.-H.; Feng, B.; Chen, Z.-W. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Lipid-lowering medications could lead to a significant reduction in major cardiovascular events in patients with diabetes. However, there was still controversy regarding the use of statins in patients with diabetes for primary prevention. The meta-analysis was performed to evaluate the outcomes of statin-therapy in diabetic patients without established cardiovascular diseases.7 randomized controlled trials of statin- vs. control-therapy in patients with diabetes were included. A total number of 12 711 patients were involved. The outcomes of interest were major adverse cardiovascular and cerebrovascular events (MACCE), including myocardial infarction, stroke, all-cause mortality and coronary revascularization.A total of 1 376 MACCE occurred during follow-up, with 9.54% (605 patients) in the statin therapy group and 12.10% (771 patients) in control group. Statin therapy was associated with a significant reduction in the incidence of MACCE (0.79, 95%CI 0.66–0.95; P=0.01). Meanwhile, the risk of stroke and coronary revascularization were reduced 29 and 26% in statin therapy group. However, there was no statistical difference of all-cause mortality between statin- and control-therapy group (3.73 vs. 4.65%, P=0.13).For primary prevention in patients with diabetes without established cardiovascular disease, statin therapy could reduce the cardiovascular and cerebrovascular events, but not all-cause mortality.
Keywords: statin; primary prevention; diabetes; coronary heart disease